FMR1 CGG repeat expansion mutation detection and linked haplotype analysis for reliable and accurate preimplantation genetic diagnosis of fragile X syndrome - Rajan-Babu, Indhu-Shree (CAMBRIDGE UNIV PRESS, 2022)
10.1017/erm.2017.10